Offshore structural reliability assessment by probabilistic procedures—a review - Syed Ahmad, S. Z. A. (MDPI, 2021)
Offshore installations must be built to resist fatigue as well as extreme forces caused by severe environmental conditions. The structural reliability analysis is the popular practise to assess a variety of natural waves determined by the long‐term probability distribution of wave heights and corresponding periods on the site. In truth, however, these structures are subjected to arbitrary wave‐induced forces in the open ocean. Hence, it is much more reasonable to account for the changed loading characteristics by determining the probabilistic characteristics of the random loads and outcomes responses. The key challenges are uncertainties and the non‐linearity of Morison’s drag element, which results in non‐Gaussian loading and response distributions. This study would analyze advances achieved to date in a comprehensive probabilistic review of offshore fixed jacket-type platforms.